Analysis of immune‐related adverse events caused by immune checkpoint inhibitors using the Japanese Adverse Drug Event Report database. Issue 10 (1st September 2020) - Hasegawa, Shiori; Ikesue, Hiroaki; Nakao, Satoshi; Shimada, Kazuyo; Mukai, Ririka; Tanaka, Mizuki; Matsumoto, Kiyoka; Inoue, Misaki; Satake, Riko; Yoshida, Yu; Goto, Fumiya; Hashida, Tohru; et al.
Abstract: Purpose: The aim of our study was to characterize the clinical features of immune‐related adverse events (irAEs) associated with immune checkpoint inhibitors (ICIs) in a real‐world setting using the Japanese Adverse Drug Event Report (JADER) database. Methods: The irAEs were defined using the preferred terms of the Medical Dictionary for Regulatory Activities. irAEs were categorized as follows: adrenal insufficiency, colitis, eye diseases, hematological disorder, hepatitis, hyperthyroidism, hypopituitarism, hypothyroidism, myasthenia gravis, myocarditis, nephritis/renal dysfunction, pneumonitis, rash, and type 1 diabetes mellitus. We used several indices such as reporting odds ratio (ROR) to assess disproportionality in pharmacovigilance data, time‐to‐onset analysis using Weibull shape parameters, and the association rule mining technique to evaluate possible risk factors between variables in the spontaneous reporting system database. Results: The JADER database contained 534 688 reports from April 2004 to June 2018. The RORs of pneumonitis including interstitial lung disease for nivolumab, pembrolizumab, and ipilimumab were 7.02 (95% confidence interval: 6.55‐7.52), 9.08 (8.28‐9.97), and 1.74 (1.27‐2.38), respectively. The median onsets (quartiles, 25‐75%) of myocarditis caused by nivolumab and pembrolizumab were 28.0 (15.5‐60.5) and 18.0 (13.0‐44.5) days, respectively. Co‐therapy with nivolumab and ipilimumab may be associated with irAEs in several categories as per the association rule mining analysis. Conclusion: Our results demonstrated a potential risk of irAEs associated with ICIs, based on RORs and time‐to‐onset analysis. Furthermore, our findings indicated that patients receiving nivolumab and ipilimumab as co‐therapy should be carefully monitored.